Pengaruh Model Pembelajaran Cooperative Learning Terhadap Hasil Belajar Siswa Di SDN 9 Limboto - Nurlatifa Dihuma; Ingka Rizkyani Akolo; Lamsike Pateda (Lembaga Pengembangan Kinerja Dosen, 2024)
The aim of this research is to measure how much influence the cooperative learning model has on student learning outcomes at SDN 9 Limboto. This research uses quantitative research methods with survey techniques to obtain complete and in-depth information regarding the influence of the cooperative learning model on student learning outcomes at SDN 9 Limboto. The population of this study were students at SDN 9 Limboto with a sample size of 104 students. Data was collected using a questionnaire, and data was analyzed using simple linear regression analysis. The research results show that the cooperative learning model has a significant effect on student learning outcomes. The model influence is 26.2% with a correlation of 51.2%. The regression model obtained from the analysis is Y = 47.392 + 0.458X. This model shows that every increase in cooperative learning by one unit will have an influence on student learning outcomes at SDN 9 Limboto by 0.458. The implications of this research show that cooperative learning has a significant influence on student learning outcomes at SDN 9 Limboto, so it is recommended that this learning model be maintained and can be collaborated with other models or media so that the model is more varied.